Review: Diagnosis of scrub typhus - Koh, G; Maude, R; Paris, D; Newton, P; Blacksell, S (2010)
Scrub typhus is transmitted by trombiculid mites and is endemic to East and Southeast Asia and Northern Australia. The clinical syndrome classically consists of a fever, rash, and eschar, but scrub typhus also commonly presents as an undifferentiated fever that requires laboratory confirmation of the diagnosis, usually by indirect fluorescent antibody (IFA) assay. We discuss the limitations of IFA, debate the value of other methods based on antigen detection and nucleic acid amplification, and outline recommendations for future study. Copyright © 2010 by The American Society of Tropical Medicine and Hygiene.